Evaluación de la producción de cerveza artesanal "Tawala" usando kiwi como fruta adicional (2018)
In the present document, the activities related to the production of beer in an artisanal way with kiwi flavor are described. A clear description was made of each of the stages required in the elaboration process such as maceration, hopping and fermentation and the moment, which was considered optimal, to add the kiwi to the base beer in such a way that it enhanced its flavor and aroma . Multiple experiments were carried out (2) to rectify the product obtained, in which its color, taste and smell were detailed, allowing to please the palate of the people selected for the tasting. These two prototypes were compared with our base beer, which is made with the same raw materials but without the presence of fruit, finding greater acceptance on the part of the tasters. To these final prototypes were carried out organoleptic studies, pH, IBUs to finally perform an analysis on the production costs of the beer.